Repurposing Plant Virus Nanoparticles - Hefferon, Kathleen L. (Vaccines (Basel), 2018)
Plants have been explored for many years as inexpensive and versatile platforms for the generation of vaccines and other biopharmaceuticals. Plant viruses have also been engineered to either express subunit vaccines or act as epitope presentation systems. Both icosahedral and helical, filamentous-shaped plant viruses have been used for these purposes. More recently, plant viruses have been utilized as nanoparticles to transport drugs and active molecules into cancer cells. The following review describes the use of both icosahedral and helical plant viruses in a variety of new functions against cancer. The review illustrates the breadth of variation among different plant virus nanoparticles and how this impacts the immune response.